Dampak Budaya Organisasi Terhadap Efektivitas Kerja Karyawan PT. Surya Kekal Mandiri Kota Gunungsitoli - Yuvan Damai Mendrofa; Sukaaro Waruwu; Peringatan Harefa; Otanius Laia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
Organizational culture has a very important influence on the progress of a company that grows through the process of developing ideas created by company leaders, then instilled in the organization. Based on the results of observations, PT. Surya Kekal Mandiri has a diverse organizational culture, one of which is less open communication. These organizational cultures have an impact on the effectiveness of employee work which is decreasing. The purpose of this study is to analyze the impact of organizational culture and work effectiveness at PT. Surya Kekal Mandiri Gunungsitoli City. The research method used in this study is quantitative with a descriptive approach. The results of this study indicate that the impact of organizational culture at PT. Surya Kekal Mandiri Gunungsitoli City is considered an innovation in doing work. This innovation can further help PT. Surya Kekal Mandiri Gunungsitoli become more efficient and effective in achieving its goals by utilizing the organizational culture, always increasing every month. And from the results of the correlation coefficient test of rxy = 0.756 which means the interval relationship of variable X (organizational culture) to variable Y (Work effectiveness) is at a significance of 0.600-0.799 indicating a strong correlation and the results of the determination coefficient test the author obtained the results of the level of influence of variable X on variable Y is 57.2% and 42.8% is influenced by other factors that are not studied in this study.